2018
DOI: 10.1016/j.bone.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone health, activity and sedentariness at age 11–12 years: Cross-sectional Australian population-derived study

Abstract: In early adolescence, MVPA duration showed associations with better bone health that, while modest, could be of population-level importance. MVPA fragmentation and sedentary behaviour duration and fragmentation seemed less important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…One study showed how that pQCT could introduce systematic error when comparing cross-sectional geometry with bone histomorphometry using different parameter thresholds. For example, threshold differences have been shown to produce variations in total cross-sectional area and bone cortical area ranging between −1%–3.1% and 4.7%–6.5%, respectively 66. SSI is particularly sensitive to overestimations as it is a composite measure that includes cortical bone area 42.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed how that pQCT could introduce systematic error when comparing cross-sectional geometry with bone histomorphometry using different parameter thresholds. For example, threshold differences have been shown to produce variations in total cross-sectional area and bone cortical area ranging between −1%–3.1% and 4.7%–6.5%, respectively 66. SSI is particularly sensitive to overestimations as it is a composite measure that includes cortical bone area 42.…”
Section: Discussionmentioning
confidence: 99%
“…Type of sport, changes (Δ, T1-T0) in maturity offset, stature, BMI, lean mass, fat mass, vertical jump, cardiorespiratory fitness, MVPA, 25(OH)D, calcium, CTX and PINP were selected as predictors based on their relationship with bone outcomes [ 5 , 12 , 31 , 32 ]. Multiple linear regression analyses were used to examine the contribution of the change in each predictor (Δ) on the change in bone outcomes (Δ).…”
Section: Methodsmentioning
confidence: 99%
“…(17,18) Polar SSI has been positively associated with MVPA but not sedentary time in Australian school-aged children. (12) This study aimed to use a 24-hour time-use approach to explore the associations between MVPA, LPA, sedentary time, and sleep with pQCT-derived measures of bone density, geometry, and strength among a large, population-based sample of Australian school-aged children. It aimed to describe the best day-the "Goldilocks Day"-for bone health, where the mix of these four behaviors is "just right" using novel analytical methods based on compositional data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…( 17,18 ) Polar SSI has been positively associated with MVPA but not sedentary time in Australian school‐aged children. ( 12 )…”
Section: Introductionmentioning
confidence: 99%